A prospective analysis of 100 consecutive lymphovenous bypass cases for treatment of extremity lymphedema - Chang, David W; Suami, Hiroo; Skoracki, Roman (Plastic and reconstructive surgery (1963), 2013)
The authors prospectively evaluated the efficacy of lymphovenous bypass in patients with lymphedema secondary to cancer treatment. The authors prospectively enrolled 100 consecutive patients with extremity lymphedema secondary to cancer treatment. Sixty-five patients underwent lymphovenous bypass with indocyanine green fluorescent lymphangiography. Evaluation included qualitative assessment and quantitative volumetric analysis before and 3, 6, and 12 months after bypass. Lymphovenous bypass was performed in 89 upper extremities and 11 lower extremities. For upper extremity lymphedemas, the mean preoperative volume differential was 32 percent. Symptom improvement was reported by 96 percent of patients and quantitative improvement was noted by 74 percent. The overall mean volume differential reduction was 33 percent at 3 months, 36 percent at 6 months, and 42 percent at 12 months after surgery. The mean volume differential reductions at 3, 6, and 12 months after lymphovenous bypass in patients with stage 1 or 2 lymphedema (58, 52, and 61 percent, respectively) were significantly larger than those in the patients with stage 3 or 4 lymphedema (12, 16, and 17 percent, respectively). Eleven bypasses were performed in seven patients with lower extremity lymphedema, with a mean preoperative volume differential of 38 percent. Only four (57 percent) of these patients reported symptom improvement; postoperative volume measurements were available for only two of these four. Lymphovenous bypass can be effective in reducing lymphedema severity, particularly in patients with early-stage upper extremity lymphedema. Indocyanine green lymphangiography accurately identified functional lymphatic vessels and may have a role in objectively assessing lymphedema severity and patient selection. Therapeutic, IV.